Penerapan Metode Simple Additive Weighting (SAW) Dalam Sistem Pemilihan Kamera Menggunakan Scratch - Dentaruni Cahya Purnomo; Indra Igun Gunawan (Jurusan Informatika STTR Cepu, 2022)
Photography is a branch of art that uses a camera as a medium for making works. Nowadays people tend to follow the trend to buy a camera to capture special moments. However, because there are so many types of cameras that are offered, choosing what kind of camera to buy will be difficult. One solution that can be used to complete camera selection is a decision support system. The purpose of this research is to apply a decision support system method, namely the simple additive weighting method into the scratch programming language to determine the best alternative camera to choose from. In this study the authors compared two cameras, namely the Canon EOS 1200D and Nikon D3300 DSL and concluded that the Canon EOS 1200D was the best alternative with a preference value of 0.94 and the Nikon D3300 DSL got a preference value of 0.89